Learners' adjustment strategies following impasses in simulations - Effects of prior knowledge. (February 2023) - Heitzmann, Nicole; Stadler, Matthias; Richters, Constanze; Radkowitsch, Anika; Schmidmaier, Ralf; Weidenbusch, Marc; Fischer, Martin R.
Abstract: After impasses, the adjustment strategies learners can use in simulations differ from the ones that are available in real-life situations. An open question is whether learners with different levels of prior knowledge use different strategies to adjust their behavior and whether the chosen adjustment strategy helps their learning. In addition, it is unclear whether adjustment strategies are stable throughout the learning process. To answer these questions, we conducted two studies that both used a medical education simulation in which a learner collaborated with an agent-based radiologist to diagnose patients. In study 1 we found that the adjustment strategy of further evidence generation was only helpful for learners with intermediate prior knowledge whereas the likelihood of an accurate diagnosis descreased for learners with low or high prior knoweledge. In Study 2, we found three relatively stable clusters: reflective learners, variable learners, and evidence generators, thus offering the potential for adaptive scaffolding. Highlights: Simulations offer other adjustment strategies after impasses than actual practice. Learners with different levels of prior knowledge profit from different adjustment strategies. Adjustment strategies after impasses are relatively stable. Impasses offer the opportunity for adaptive scaffolding.